Socio-Economic Dynamics at the Border: A Case Study of the Sota, Merauke Cross-Border Post and Its Implications for Cooperation with Papua New Guinea - Melyana Ratana Pugu; Mathilda Pusung (Journal of Social Research, 2025)
This study examines the socio-economic dynamics in the Indonesia-Papua New Guinea border area, focusing on the Sota Cross-Border Post (PLBN) which was built in 2019 and inaugurated in October 2021. The purpose of this study is to analyze the impact of PLBN on socio-economic changes in the border communities of Sota and Weam, as well as its implications for Indonesia-Papua New Guinea bilateral cooperation. The method used is qualitative research with a case study approach, which involves in-depth interviews, participatory observations, and documentation studies. The results of the study show that before PLBN, border communities depended on subsistence activities such as agriculture, hunting, and traditional trade. The existence of PLBN brings significant changes in the aspect of cross-border trade, opens up wider market access, and creates new opportunities in the trade and small business sectors. However, the challenges of infrastructure management and limited human resource capacity at the local government level are still the main obstacles. PLBN Sota has the potential to become a new economic growth center in South Papua, with a sustainable development strategy that involves strengthening infrastructure and the capacity of local communities.